2020
DOI: 10.1002/mar.21326
|View full text |Cite
|
Sign up to set email alerts
|

The effects of online negative word‐of‐mouth on dissatisfied customers: A frustration–aggression perspective

Abstract: Conceptualizing how customers construe online negative word‐of‐mouth (nWOM) following failure experiences remains unsettled, leaving providers with inconclusive recovery strategy programmes. This empirical study recognizes online nWOM as a co‐created encounter between the complainant (i.e., the initiator of the online nWOM) and the recipient (i.e., the consumer who engages with the online nWOM), examining their idiosyncrasies to discern their understanding of the experience. It introduces frustration–aggressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 73 publications
(145 reference statements)
0
53
0
Order By: Relevance
“…Third, it shows the effect of PCE on AGB and NWOM about banks that disregard the environment, following the need to have a greater understanding of PCE (Kang et al., 2013; Kautish et al., 2019). Fourth, it shows the mediating role of NWOM on the effect of PCE on IGB, following the need to advance understanding regarding negative word‐of‐mouth (Azemi et al., 2020). Finally, it shows the effect of NWOM about banks that disregard the environment on IGB, following the need to promote green banking services (Bryson et al., 2016; Lymperopoulos et al., 2012; Patterson & McEachern, 2018) that increase the consumers’ well‐being (Atik et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Third, it shows the effect of PCE on AGB and NWOM about banks that disregard the environment, following the need to have a greater understanding of PCE (Kang et al., 2013; Kautish et al., 2019). Fourth, it shows the mediating role of NWOM on the effect of PCE on IGB, following the need to advance understanding regarding negative word‐of‐mouth (Azemi et al., 2020). Finally, it shows the effect of NWOM about banks that disregard the environment on IGB, following the need to promote green banking services (Bryson et al., 2016; Lymperopoulos et al., 2012; Patterson & McEachern, 2018) that increase the consumers’ well‐being (Atik et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Third, PCE is an important variable in the understanding of green consumer behaviour as indicated by its role in affecting AGB and NWOM about banks that disregard the environment, thus supporting the literature on PCE (Kang et al., 2013; Kautish et al., 2019). Finally, NWOM can be used to predict large scale, aggressive potential harm by the customers against a service provider as indicated by their choice preferences that differ from the previous ones (Azemi et al., 2020; Patterson & McEachern, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thompson, 1997). Hermeneutic and phenomenological lenses have been fruitful in prior research when exploring consumers' realities, including how they construct identity (Ahuvia, 2005;Azemi et al, 2020). Previous research has found that interviewees are reluctant to share rich identity-related information in group settings, so data were collected in one-on-one interviews (Bisogni et al, 2002).…”
Section: Qualitative Design and Data Productionmentioning
confidence: 99%